Looking closely: An analysis of resources in course syllabi of the Graduate School of Business - Natividad, Karen Cecille V. (Animo Repository, 2018)
Resource analysis in course syllabi aids collection managers in future resource selection and identification of titles for evaluation for possible inclusion in the collection. The study seeks to analyze the resources in course syllabi used by faculty members teaching graduate courses in the RVRCOB. All listed references were entered into a spreadsheet by a group of library staff identifying their resource type, availability in the library collection, and publication year. Percentage distribution was used to determine the needed data. Despite the implementation of full online classes, print books comprised the most significant percentage of resource type in syllabi. This was, however, complemented by journal articles and websites having the second and third largest percentage, respectively. Journal titles listed in the syllabi were all available in the library collection either in print or electronic format yielding 100% availability for the said resource type. Electronic journal articles have the second-highest percentage of availability with 81.46%. Finally, the study revealed that most of the resource materials used were published between the last 6-10 years or 2012-2016 and materials with no or identified publication date comprised the second- highest percentage, most of which were websites. The majority of the references listed in the course syllabi were print materials suggested several indications- (1) faculty members are yet to adapt to the new normal in education fully; (2) faculty members’ comfort zone is still with the print materials; (3) they are not aware of the availability of materials in electronic format in the library collection; and (4) there may be not enough electronic resources to support their course. The small percentage in the available resources in the library collection suggested an insubstantial collaboration between the faculty. With this, it is recommended to explore other ways to involve faculty in selection and to strengthen collaboration with them to ensure resources are readily available to the students. Titles not available in the library must be reviewed in collaboration with the faculty for purchase or subscription possibility. Lastly, assessment of electronic collection, especially e-books, along with their intensive marketing and promotion must also be in line to ensure the library's readiness to support online teaching and learning fully.